(untitled) (Research, Society and Development, 2020)
The objectives of this study are to identify what are the actions that constitute nursing care in hemodynamics in scientific publications and to analyze the nurse’s duties in caring for patients undergoing interventional cardiological treatment in scientific publications. It is an integrative review study with a quantitative approach, the data collection instrument used to organize the content obtained in the references was a table containing the following items: per year, database, methodology, content essence and knowledge production , and authors’ recommendations. In the results obtained through the analysis of articles, it was possible to understand the nursing actions in the hemodynamics service through the view of several authors. We found in the databases BDENF, LILACS, MEDLINE, PUBMED, CINAHL, COCHRANE and Scielo 188 articles with the combination of descriptors: Nursing and Cardiology and Hemodynamics. In total, 9 articles were included. Thus, it is concluded that the nurse’s performance in Hemodynamics is essential to identify problems and solutions in the health-disease process, because before, during and after cardiac procedures, whether this diagnosis or treatment, the nurse must pay attention to factors that permeate the patient, so that a targeted care plan and quality care can be elaborated.